"They are all alike": When negative minority outgroups are generalized onto superordinate inclusive outgroups. (November 2019) - Albarello, Flavia; Foroni, Francesco; Hewstone, Miles; Rubini, Monica
Abstract: Two studies investigated outgroup-to-outgroup generalization, addressing whether members of negatively perceived minority outgroups are perceived as prototypical of larger partially-inclusive outgroups and whether this tendency is enhanced under intergroup threat. Both experimental studies were conducted with Italian undergraduate participants. Experiment 1 ( N  = 186) tested whether Roma are generalized onto (i.e., perceived as prototypical of) Romanians to a higher extent under intergroup realistic and symbolic threat than under no-threat. It also explored the direction of the phenomenon and its underlying mechanism. Experiment 2 ( N  = 90) provided additional evidence on the effect of threat on such generalization phenomenon considering a different pair of groups (Islamic terrorists, Arabs) and employing a less blatant measure of generalization. Overall, these studies provided consistent evidence of outgroup-to-outgroup generalization, clarifying the conditions of its occurrence. These results contribute to the understanding of the phenomenon of outgroup-to-outgroup generalization and of its impact on outgroup perception and prejudice.